Correlações da Teoria da Representação e Teoria da Intencionalidade: contribuições para a Encontrabilidade da Informação - Sanchez, Fernanda Alves [UNESP]; de Castro, Fabiano Ferreira [UNESP]; Vechiato, Fernando Luiz [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (IBICT, 2023)
The Theory of Representation and the Theory of Intentionality are concepts arising from areas of knowledge such as Psychology, Philosophy and Cognitive Sciences. In the field of Information Science, Information Representation is an already consolidated concept, however, there are few works on the Theory of Intentionality. In view of the post-custodial paradigm, it is possible to affirm that informational subjects are active individuals in the socio-informative scenario, who apply their intention to produce, organize, represent and search for information in different types of digital informational environments. As an objective, the research sought to identify the existing correlations between the theories of Representation and Intentionality in the context of Information Science, aiming to verify which contributions to the Findability of Information - a concept whose approach includes theoretical-practical perspectives for projects, implementations and evaluations of informational environments. This is research that presents itself as bibliographical and exploratory and with a qualitative approach in databases such as Portal in Periodicals of Capes, the Database on Information Science (BRAPCI) and Google Scholar. Among the research results, it was possible to identify correlations in the concepts of Representation Theory and Intentionality, as well as the importance of the foundations of these concepts to enhance the Findability of Information. Finally, it is concluded that there is a need to deepen studies on Intentionality in ​​Information Science, given the scarcity of research, in addition to its relevance in bringing the positioning of the informational subject within the concept of Information Findability.
Keywords: Digital information environments; Information Findability; Information Representation; Intentionality of informational subjects